Sludge composting production line - LI MIANSHENG; YANG CHUNGUANG (2015)
The utility model discloses a sludge composting production line. The sludge composting production line comprises a stirring device provided with a feed port, a continuous conveying device used for conveying sludge into the feed port of the stirring device, and a microbial agent pumping device used for adding microbial agents to the sludge. The microbial agent pumping device comprises a liquid storage tank, a nozzle and a feed pump, wherein the nozzle is arranged at the tail end of the continuous conveying device and is located above the feed port, and the feed pump can pump the microbial agent inside the liquid storage tank to the nozzle. According to the sludge composting production line, the device for adding microorganisms is selected at the tail end of the continuous conveying device, in other words, the continuous conveying device is arranged at the blanking position above the feed port of the stirring device, the microbial agents are conveyed to the blanking portion at the tail end of the continuous conveying device by the feed pump through two high-pressure net pipes, and then the nozzle is connected and performs spraying in the direction aligned with the blanking direction. Thanks to the sludge composting production line, the utilization rate of microorganisms is high, and contact in even.